Cultivating an Inclusive Culture Through Personal Networks - Cross, Rob; Cross, Rob; Oakes, Kevin; Cross, Connor (MIT Sloan Management Review, 2021)
Early analysis of racial and networking data in 10 organizations highlights three behavioral drivers of inclusion: establishing ties with colleagues and stakeholders early on, building networks with diverse “bridging” ties, and seeking out mentoring. These behaviors were associated with faster promotions and longer tenures for employees of color.